If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -5) + (x + -5) = 0 Reorder the terms: x(-5 + x) + (x + -5) = 0 (-5 * x + x * x) + (x + -5) = 0 (-5x + x2) + (x + -5) = 0 Reorder the terms: -5x + x2 + (-5 + x) = 0 Remove parenthesis around (-5 + x) -5x + x2 + -5 + x = 0 Reorder the terms: -5 + -5x + x + x2 = 0 Combine like terms: -5x + x = -4x -5 + -4x + x2 = 0 Solving -5 + -4x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -1x)(5 + -1x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-1, 5}
| 4=0.6s | | 11x^2-2x+9=62 | | 4n+5-2n+10=49 | | A(n)=4+(n+1)(6) | | z^5=0 | | 15.35+10.25c=425.35 | | -3(4x+3)+4(6x+1)=43+4x | | (149-3x)=(5x+12) | | 1+14i= | | 5n^2-58n+80= | | 2x-6+2x-6+x+3+x+3=26 | | 3(-x-3)=4x-2(x+1) | | 25m+.45=40m+.25 | | t-(8*8+0.36)=0.5 | | 3(-x+3)=4x-2(x+1) | | 4t+9=8-13 | | -7.5+5.5(1+9d)=-17.5 | | 15.35+10.25c=353.6 | | 1.4n+4*4*4=85 | | 2m^2-7m+3= | | x^2-2x-240=0 | | 3x-35=128 | | -27.5+4c=-28.5-3y | | 99+x=189 | | 10x+20+12x=180 | | 13x+2=2x+2 | | 5x*8y=12 | | 52-3*7=62 | | 23.99x+120.84x=675.28 | | 3[2p-5]=33 | | 7.5(7y-5)=-28.5-3y | | 8-3a+8a-8b+3b= |